Desain Edible Landscape, Bentuk Pertanian Kota Yang Meningkatkan Estetika Dan Ketahanan Pangan - Fabiola B. Saroinsong (AGRI-SOSIOEKONOMI, 2022)
Edible landscape is one of the multifunctional approaches in landscape planning specifically urban agricultural landscape planningbecause it can increase the beauty of the area and at the same time strengthen local food security, as well as other ecological, social and economic functions. Various choices of edible landscape designs are needed that take into account space limitations to support effective and efficient land use. The purpose of this paper is to provide several choices of edible landscape designs, especially for urban areas in improving aesthetics and food production. The research was carried out from mid-July to the end of August 2022. The data collection method used the documentation method through the collection of literature studies related to the edible landscape. The design method (design creation) is carried out through the stages of preparation, inventory, analysis, synthesis, concept generation, planning, and design (Saroinsong, 2022). Several designs were made to be an option or reference for the idea of developing an edible landscape in urban areas. To increase community support and involvement, the design took into account the limitations of land, the principle of multifunctionality, ease of cultivation and harvesting, and emphasized that the selection of edible plants is related to the daily lives of local people. The conclusion of this research is that the edible landscape design applies the concept of multifunctional land and approaches to community involvement and empowerment.